UMPA offers programmes to encourage industry workers continue study - Siti Nurfarmy, Ibrahim (2021)
KUANTAN, 4 July 2021 - Underlying the Malaysia Education Blueprint 2013-2025, UMP Advanced Education (UMP Advanced) is cultivating and expanding educational initiatives to Sijil Pelajaran Malaysia (SPM) or diploma holders and also to workers through flexible learning.